The Oxford handbook of the radical right - Rydgren, Jens 1969- HerausgeberIn (Oxford handbooks, 2018)
The resurgence of strong radical right-wing parties and movements constitutes one of the most significant political changes in democratic states during the past several decades, particularly in Europe. The radical right's comeback has notably attracted interest from political scientists, sociologists, and historians, although the majority of past research focuses on party and electoral politics. In contrast, The Oxford Handbook of the Radical Right not only covers existing literature, but also shows how the radical right forms movements rather than parties. Editor Jens Rydren has gathered an international cast of contributors to cover concepts and definitions; ideologies and discourses; and a range of contemporary issues such as religion, globalization, gender, and activism. Further, this volume is one of few to provide a number of cases focusing on areas outside of Europe, including Russia, the US, Australia, Israel, and Japan. By integrating various strands of scholarship on the radical right that covers different regions and different research perspectives, this Handbook provides an authoritative and state of the art overview of the topic and will set the agenda for scholarship on the radical right for years to come.